TUTORING AS A MEANS OF INDIVIDUALIZING THE EDUCATIONAL PROCESS: AN EXPERIMENTAL STUDY - Vyshkivska, Vanda; Sylenko, Yuliia; Shykyrynska, Oleksandra; Myroshnychenko, Viktoriia; Shevchenko, Viktoria; Kozlov, Yevhen (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The new information type of society has qualitatively changed the concept of training future specialists. Currently, technocratic relations in the "teacher-student" system are being replaced by humanistic ones, with a transition to cooperation with students as active subjects of the individualized educational process. The authors of the article, taking into account the European experience of individualizing education, analyzed the peculiarities of using tutoring technology as a means of individualizing the education of master's students in the conditions of mixed education. The results of the ascertaining stage of the pedagogical experiment, the participants of which were teachers and master's students of Dragomanov Ukrainian State University (Kyiv), National Technical University “Kharkiv Polytechnic Institute” (Kharkiv), Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University (Vinnytsia), are presented. The purpose of the confirmatory experiment was to identify the level of understanding of university teachers, as well as master's students – future teachers of the essence of tutoring technology and the presence of experience in using it in professional activities. The article proves that the use of tutoring technology in conditions of mixed learning allows students of higher education to gain experience in independent planning, obtaining and improving educational results. It is substantiated that the acquisition of such experience takes place during the work of tutors (with systematic tutoring support) on individual tutorials, which contain multi-level complex tasks from a certain educational subject. The role and place of the scientific essay as a component of tutoring technology and as a means of individualizing the educational process, which ensures the development of independent creative thinking of students, the formation of their ability to structure information, skillful presentation of arguments, establish cause-and-effect relationships, and formulate conclusions, is characterized.